On the History of Choice: William Dean Howells and the Roots of the Neoliberal Individual - Benack, Carolin (ELH, 2023)
The neoliberal individual, according to critics like Wendy Brown and Michel Foucault, treats all spheres of life as subject to utility maximization: Whether deciding on a job, a house, or a romantic partner—everything is treated according to a logic of economy. Scholars typically point to economics as the conceptual source of this subject. In this essay, I suggest a different point of origin: the late-nineteenth century novel. Taking a classic of American realist fiction, William Dean Howells's The Rise of Silas Lapham (1885), as representative for a larger trend, I show that the novel both articulates and evinces a shift in the cultural conception of the individual. Silas Lapham reorients the individual away from the liberal subject, primarily defined by property ownership, and toward the incessantly choosing entity of neoliberalism. This essay at once reframes existing discussions of the neoliberal subject and shows that neoliberal thought has long been articulated by entities other than economics—namely, novels.